2004
DOI: 10.1002/ijc.11662
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of VEGF, HIF1α and angiopoietin‐1, ‐2 and ‐4 by hypoxia and ionizing radiation in human glioblastoma

Abstract: We examined how ionizing radiation (IR) delivered under either severe hypoxia (< 0.1% O 2 ) or normoxia affects the expression of hypoxia inducible factor 1␣ (HIF-1␣) and the angiogenic factors vascular endothelial growth factor (VEGF) and angiopoietins 1, 2 and 4 in U87 human glioblastoma cells. IR was delivered as single doses of 0, 2, 5, 10 and 20 Gy after 6-hr hypoxic incubation and in normoxic controls. Irradiation at any dose did not affect the cellular protein levels of any of the angiopoietins, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 18 publications
(16 reference statements)
1
43
0
Order By: Relevance
“…VEGF expression and vessel density decreased after low-dose XRT, while HIF-1a expression showed no obvious change, Lund et al also reported that VEGF upregulation occurred from 18 to 24 hr after 5Gy ionizing radiation, whereas 2Gy ionizing radiation had no effect on the expression of VEGF from 18 to 24 hr after radiotherapy. 26 HIF-1a expression was markedly suppressed by rhK5 treatment and its level was highly correlated with vessel density. It was noted that failure of tumor control in radiotherapy was due to increased radioresistance of endothelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…VEGF expression and vessel density decreased after low-dose XRT, while HIF-1a expression showed no obvious change, Lund et al also reported that VEGF upregulation occurred from 18 to 24 hr after 5Gy ionizing radiation, whereas 2Gy ionizing radiation had no effect on the expression of VEGF from 18 to 24 hr after radiotherapy. 26 HIF-1a expression was markedly suppressed by rhK5 treatment and its level was highly correlated with vessel density. It was noted that failure of tumor control in radiotherapy was due to increased radioresistance of endothelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, we tested whether CCI-779 reverses the release of hypoxia-inducible factor (HIF)-1-driven VEGF that becomes increased in response to ionizing radiation and hypoxia (Lund et al, 2004;Tabatabai et al, 2006). Inhibition of mTOR markedly suppressed HIF-1 production induced by irradiation or sublethal hypoxia and reduced VEGF levels (Fig.…”
Section: Irradiation-enhanced Mtor Inhibition Exerts Combined Antiangmentioning
confidence: 99%
“…The hypoxic region in tumors required higher radiation doses to obtain similar biologic effects compared with normoxic regions (Lund et al, 2004). In hypoxic conditions, tumor cells would undergo gene mutation to adequate the circumstances they lived, which resulted in the radioresistance.…”
Section: Introductionmentioning
confidence: 99%